2021
DOI: 10.3390/insects12030264
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Accumulated Degree-Days and Entomological Approaches in Post Mortem Interval Estimation

Abstract: Establishing the post mortem interval (PMI) is a key component of every medicolegal death investigation. Several methods based on different approaches have been suggested to perform this estimation. Among them, two methods based their evaluation on the effect of the temperature and time on the considered parameters: total body score (TBS)/accumulated degree-days (ADDs) and insect development. In this work, the two methods were compared using the results of minPMI and PMI estimates of 30 forensic cases occurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…The scores from each region are summed together to provide a numeric value representing decomposition progress. TBS can be compared with temporal measures of time or other measures incorporating time and temperature (accumulated degree days, ADD ) to provide a model-based approach for PMI estimation [ 13 ]. The reliability of this method to produce accurate PMI estimates has been questioned [ 14 , 15 ], which has led to the development of more complex TBS models to improve accuracy and reliability [ 9 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The scores from each region are summed together to provide a numeric value representing decomposition progress. TBS can be compared with temporal measures of time or other measures incorporating time and temperature (accumulated degree days, ADD ) to provide a model-based approach for PMI estimation [ 13 ]. The reliability of this method to produce accurate PMI estimates has been questioned [ 14 , 15 ], which has led to the development of more complex TBS models to improve accuracy and reliability [ 9 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…All of these models could be used to estimate the PMImin; however, the biology of the insects and the climatic parameters under which they are dynamic should be considered [37]. In addition, to provide an accurate PMI, Shang et al [28] suggested the use of a multimethod combination, as well as a combination of multidisciplinary specialists, to analyze and interpret data from forensic investigations [95]. Therefore, further research is still required to test other methods using this species.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been developed to estimate the PMI of cadavers in different stages of decay. However, accurate estimation can be challenging, especially when dealing with corpses in advanced stages of decomposition [ 1 , 2 , 3 , 4 , 5 ]. Several postmortem (PM) markers can be used to ascertain the time elapsed since death in the initial PM period.…”
Section: Introductionmentioning
confidence: 99%